Mediating Effect of Comfortable and Durability, Feature and Aesthetic and Reliability of Product on Price and Product Purchase Decision: Study at One Retail Company in Bandung - Juhana, Dudung (Acman: Accounting and Management Journal, 2023)
This study aims to examine the mediating influence of product comfort and durability, product features and aesthetics, and product reliability on the relationship between product price and purchasing decisions for children's clothing products in Bandung City. This study employs a survey research methodology, which entails gathering data from a sample of 100 participants actively engaged in consuming children's clothing products. The findings derived from examining data through exploratory factor analysis (EFA) and path analysis indicate a noteworthy impact of product price on Comfort and durability, Features and Aesthetics, and Product Reliability. Moreover, the research findings suggest a substantial mediating effect of Product Comfort, Durability, and Reliability on the association between product price and purchasing decisions. This finding suggests that the impact of price on consumers' choices to purchase a product can be mainly attributed to its influence on perceived factors such as comfort, durability, and product performance. Nevertheless, it is worth noting that there is no substantial evidence to suggest that Features and Aesthetics play a significant role in mediating the connection between price and consumers' decisions to purchase a product. This finding suggests that within the domain of children's clothing products, certain features and aesthetic qualities do not necessarily ensure the Comfort, Durability, and Reliability factors play a significant role in shaping consumer purchase choices. This study offers significant insights for marketers and makers of children's apparel goods in the urban area of Bandung. It highlights the significance of comprehending the interplay between customer perceptions of price, comfort, and durability in shaping purchasing choices. The employed research methodology involves exploratory factor and route analysis, enabling researchers to delve into the intricate connections between variables and the mediating function they play with greater precision. This study additionally establishes a basis for enhanced marketing tactics and a more comprehensive comprehension of customer inclinations within children's apparel merchandise.